Dual elements isolated Magnetic Dipole MIMO Antenna with semi circular slot structure for isolation enhancement / Mohd Aziz Aris...[et al.] - Aris, Mohd Aziz; Ja’afar, Hajar; Abdullah, Rina; Jaafar, Afiza Nur; Mohd Redzwan, Fatimah Nur (2020)
This project is presenting preliminary research in designing the Isolated Magnetic Dipole (IMD) MIMO Antenna for wireless application. Isolated Magnetic Dipole structure is one of the unique geometries that offers compact and low damaging electrical current at the ground surface. However, less attention in discussing design the MIMO antenna using IMD structure. The two elements MIMO antenna using IMD with linear port configuration has been constructed at 2.4 GHz. Then simulated and analyzed has been carried out to validate the feasibility of the IMD-MIMO antenna. The simulation and analysis cover S-parameters, radiation, gain, correlation coefficient and diversity gain. In addition, simple semi-circle structure etched on the ground layer to improve the isolation of MIMO antenna. From the simulation results, the IMD-MIMO antenna provide better results and highly recommended for designing compact MIMO antenna.